A COLLABORATIVE MODEL FOR SUSTAINABLE COCOA PRODUCTION - Karim, Ikawati; A. Syahrir, Nur Hilal; Wulandari, Eliana; Arsal, Ariady; Paliszkiewicz, Joanna (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Cocoa in Indonesia nowadays faces some problems including in West Sulawesi which decreased the quality and quantity of cocoa bean. To enhance sustainability through high-quality cocoa production due to the supply of global market demand, it is important to elaborate a collaborative model between two-partner or more.  As a purpose, this study focuses to measure the collaborative model between local cocoa farmers and Swisscontact through the Sustainable Cocoa Production Program (SCPP) in economic, environmental, and social dimensions. Primary data were collected by random sampling of 269 local cocoa farmers at the center of the Sustainable Cocoa Production Program (SCPP). Data were formulated using a scatterplot diagram, pearson correlation, multiple regression, and confirmatory factor analysis through the indicator in economic, environmental, and social dimensions. This paper provides a model of collaboration in which it bargains for stakeholders such as government both local and national, other policymakers, and private sectors to apply for sustainability programs in cocoa production. This model specifically showed a fit and good relationship between two partners as well as a good level of acceptance for the sustainable cocoa production program. Therefore, the origin found that collaboration would be a sophisticated model to be applied to the local cocoa farmers due to increasing their income, reducing the negative impact of environment and improving the quality standard of life.